“Title” And “Judiciary Power Based On Law Number 48 Of 2009” - Tedy Subrata (LEGAL BRIEF, 2022)
Judicial Power, based on Law Number 48 of 2009, is the power of an independent state to administer justice to uphold law and justice based on Pancasila for the sake of the implementation of the Republic of Indonesia. The state judiciary implements and enforces law and justice based on Pancasila. The trial was conducted "FOR JUSTICE BASED ON THE ONE ALMIGHTY GOD." In the profession of a judge, all rules are regulated in the Code of Ethics and Conduct of Judges (KEPPH) and Law Number 48 of 2009 concerning Judicial Power. Any interference in judicial matters by other parties outside the judiciary's power is prohibited except in cases referred to in the 1945 Constitution of the Republic of Indonesia. Courts try according to the law without discriminating against people. This research was carried out in a normative juridical manner by examining the object or research target in the form of regulations, legislation, and other legal materials related to the prohibition of judges examining cases with a kinship relationship.